Strategic Role of the Pharmaceutical Industry in the Сontext of the Global Pandemic - Z. A. Mamedyarov (Международная аналитика)
The strategic importance of the pharmaceutical industry for the scientific, technological and economic development of countries determines its impact on international processes. The paper traces the current trends in the growth of innovative competition in pharmaceuticals and biotechnology, taking into account the factor of the COVID-19 pandemic. The following areas of increased competition are highlighted: diversification of supply of active pharmaceutical substances, regulators’ permission of the newest drugs to access the market, competition of pharmaceutical companies for capital and competence. The pandemic has also exacerbated long-standing problems: the efficiency of drug distribution to citizens, the dependence of large manufacturers on active substance suppliers from China, drug pricing, and the role of social insurance systems in developed and developing countries. The article analyzes the main problems of the industry and presents possible trajectories of further development of international relations in the context of pharmaceuticals and biotechnology, analyzing the progress of creation and market admission of COVID-19 vaccines. For all the high-tech trends, the pharmaceutical industry is a rather conservative industry in which regulatory issues play a significant role. Therefore, legal, ethical and practical issues related to the collection of sensitive patient health data may slow down the digitalization of the pharmaceutical industry. Much will also depend on the decisions of major regulators – in the U.S. and the EU – regarding telemedicine and digital health in general. A serious barrier for the pharmaceutical industry is also the lack of pharmaceutical companies’ own experience in developing software solutions, which makes them dependent on external suppliers of IT solutions, complicates the problem of sharing clinical patient data and particularly raises the issue of cybersecurity.